Advances in multimedia information processing – PCM 2015 : 16th Pacific-Rim Conference on Multimedia Gwangju, South Korea, September 16-18, 2015, Proceedings.: 16th Pacific-Rim Conference on Multimedia Gwangju, South Korea, September 16-18, 2015, Proceedings. Part I ([2015]) - Unknown
No abstract available